Incidencia del cambio de usos de suelo en el azolvamiento del embalse la Esperanza, cantón Bolívar, Manabí - Calderón Pincay, José Manuel (2015)
The presented a study to determine the impact of land change in the La Esperanza dam silting during the period of 1995 - 2014. This study uses descriptive, historical and comparative methods in order to evaluate changes in land use before and after or during the period mentioned, in addition to field techniques such as direct observation it determined conditions of contributing watersheds current; surveys and statistics such as mean and variance for data processing and visualization of the results complemented with GIS tool through ArcGIS software version 10.2.1., in which the maps were created expressing changes in soil use. The results indicate that the main change in land use is the tropical forest to agriculture either by relatives or pasture crops; the rate of deforestation in the study area was 0.091% equivalent to 733.08 ha / year while the value of the sediments was 200 797 002 million m3, which was obtained by applying the universal soil Loss equation and the difference in volumes of initial and current reservoir water. Thanks to the contrast of the variables in the SPSS software the graph obtained confirmed that changes in land use being an adversely effect of siltation for the reservoir La Esperanza, thus confirming the hypothesis of the research.